1998
DOI: 10.1128/jvi.72.11.9396-9399.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Human T-Cell Leukemia Virus Type 1 Oncoprotein Tax Inhibits the Transcriptional Activity of c-Myb through Competition for the CREB Binding Protein

Abstract: Tax, the transforming protein of human T-cell leukemia virus type 1 (HTLV-1), is required for strong activation of HTLV-1 transcription. This activation is mediated through interaction with the KIX domain of the cellular coactivator CREB binding protein (CBP). In this study we examined the possibility that the Tax-KIX interaction may mediate effects on cellular gene transcription in vivo, as a growing number of cellular transcription factors have been shown to utilize CBP as a coactivator. We tested the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Let-7i, miR-132, miR-199a) of many host cellular miRNAs [67]. The modulation of these host miRNAs has an effect on the expression of cellular proteins such as p300, NF-kB, and BRM, to name a few, which are all recruited by Tax and play a key role in activating HTLV-1 gene transcription [5,[30][31][32][33][34][35][36][38][39][40][44][45]56,60,[68][69][70][71]. To better define the functional significance of Drosha downregulation by Tax, we transfected 293T cells with pACH.Tax (5 mg) and 24 hours later added back pGFP-Drosha (10 mg).…”
Section: Suppression Of Cellular Mirnas By Htlv-1 Can Be Rescued By Omentioning
confidence: 99%
See 1 more Smart Citation
“…Let-7i, miR-132, miR-199a) of many host cellular miRNAs [67]. The modulation of these host miRNAs has an effect on the expression of cellular proteins such as p300, NF-kB, and BRM, to name a few, which are all recruited by Tax and play a key role in activating HTLV-1 gene transcription [5,[30][31][32][33][34][35][36][38][39][40][44][45]56,60,[68][69][70][71]. To better define the functional significance of Drosha downregulation by Tax, we transfected 293T cells with pACH.Tax (5 mg) and 24 hours later added back pGFP-Drosha (10 mg).…”
Section: Suppression Of Cellular Mirnas By Htlv-1 Can Be Rescued By Omentioning
confidence: 99%
“…This occurs through transcriptional induction of TREs, posttranslational modifications of TRE-binding factors, and binding with transcription factors. Tax is known to interact with the transcription factors CREB, serum-responsive factor (SRF), and NF-kB as well as with the cell cycle related proteins Cyclin D2 and D3, mitotic checkpoint regulators (MAD1), cyclin-dependent kinases (cdks), cdk inhibitors p16 INK4a and p21/waf1, and p53 [5,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Phosphorylation of Tax is necessary for Tax localization in nuclear bodies as well as activation of cellular gene expression through the NF-kB pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Tax protein recruits DNA-binding cellular proteins including ATF/CREB, which associates with the CREB-binding protein (CBP)/p300 (14,15), in complexes that facilitate access to the TREs. Tax protein also directly binds the transcriptional coactivators, CBP/p300 (16)(17)(18)(19)(20) and P/CAF, (21), both proteins containing intrinsic histone acetyltransferase (HAT) activity (22). It has been shown that HAT enzymes lead to histone acetylation and promote transcription in part by relaxing specific nucleosomal-DNA interactions, facilitating the binding of transcription factors to their target gene promoters.…”
Section: Introductionmentioning
confidence: 99%
“…p300 mediates the activities of various transcription factors; however, its availability in the cell is limited (Petrij et al, 1995). A variety of cellular proteins are known to compete with each other for binding to p300 (Colgin and Nyborg, 1998). This environment of competition between transcription factors for co-activator binding provides an additional layer of tightly regulated gene expression.…”
Section: Introductionmentioning
confidence: 99%